Genghis Khan's Effect on the Muslim World (American Journal of Islam and Society, 2006)
Books Reviewed: Jack Weatherford, Genghis Khan and the Making ofthe Modern World. New York: Crown Publishers, 2004; Thomas T. Allsen,Culture and Conquest in Mongol Eurasia. UK: Cambridge University Press,2001; Justin Marozzi, Tamerlane: Sword of Islam, Conqueror of the World.London: HarperCollins, 2004.What these books have in common is their attempt to recast our perceptionsof the Mongols’ impact upon the Islamic world. Given the lore of gorethrown up by the intervening centuries, the authors clearly had their workcut out for them. Over the course of those centuries, hardly a schoolchild oreven an illiterate villager anywhere in the Islamic world, and certainly inMuslim Central Asia, was not taught to dread and despise the very mentionof the Mongols – and especially their two most infamous and notorious leaders,Genghis Khan and Tamerlane. To a great degree, the same holds true forchildren in other parts of the world, especially in Europe, where the worksof Chaucer, Marlowe, and others contributed greatly to the vilification ofthese two Mongols. After reading the three books under review, there is no option for thecareful reader but to reassess his/her own understanding of the Mongol centuries(the thirteenth and fourteenth CE) and, indeed, of how history mayrightly or wrongly be represented and perceived. Much of the informationpresented in these books is truly eye-opening. There is probably just as muchthat is ultimately material for continued scholarly consideration and interpretation.However, it is at the human level that any such reading must begin.If history is really a matter of perspective, let me begin by quoting fromJustin Marozzi’s work:Such cultural benefits to Persia of Mongol rule were all very well. But, asDavid Morgan concluded in a recent study of medieval Persia: “We mayjustly have our doubts over how impressed the Persian peasants, as theydid their best to avoid the Mongol tax-collectors, would have been bydevelopments in miniature painting. For Persia, the Mongol period was adisaster on a grand and unparalled scale.” ...